2005
DOI: 10.1042/bst0330418
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood cells and their microparticles in blood coagulation

Abstract: The transmembrane glycoprotein TF (tissue factor) plays an essential role in haemostasis as the principal initiator of blood coagulation. In this paper, we describe how the circulating blood cells--monocytes, platelets, neutrophils and their microparticles--co-operate in regulating the expression, availability and activity of monocyte-derived TF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Of relevance, the effect of indobufen on TF was also observed in whole blood monocytes exposed to LPS, an experimental condition characterized by the cooperation between monocytes and other cells/cell microparticles in terms of TF induction [55].…”
Section: Discussionmentioning
confidence: 98%
“…Of relevance, the effect of indobufen on TF was also observed in whole blood monocytes exposed to LPS, an experimental condition characterized by the cooperation between monocytes and other cells/cell microparticles in terms of TF induction [55].…”
Section: Discussionmentioning
confidence: 98%
“…Under physiological conditions, the density of surface anionic phospholipids is not sufficient to support initiation of a coagulation cascade but in response to triggers able to cause injury and activation such as thrombin (Qu et al, 1996), viral infections (van Geelen et al, 1995 or hyperlipidemia (Lupu et al, 1993), endothelial cells expose PS not only as an early feature of apoptosis. Additionally, microparticles carrying these phospholipids and TF on the surface are shed into the circulation by activated endothelium, platelets and leukocytes (Eilertsen and Osterud, 2005) and contribute to increased risk of thrombotic events.…”
Section: Annexin A5 As An Anticoagulant and Antithrombotic Proteinmentioning
confidence: 99%
“…Previous studies have shown that the presence of TF-bearing MPs is associated with an increased risk of thromboembolic events in malignancy (Zwicker et al, 2009). Apart from the TF-bearing MPs derived from tumour cells, endothelial cells as well as monocytes and platelets can also be triggered to release MPs (Horstman et al, 2004;Eilertsen and Osterud, 2005;Piccin et al, 2007;Morel et al, 2011;Owens and Mackman, 2011;Angelillo-Scherrer, 2012;Delabranche et al, 2012;McVey et al, 2012). There is an ongoing discussion as to whether the components of these PAR-activating complexes are decisive for specific signalling functions (Ahamed et al, 2006;Pendurthi et al, 2007;Reinhardt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%